Influence of age, sex, plaque and smoking on periodontal conditions in a population from Bauru, Brazil Influência da idade, sexo, placa bacteriana e fumo nas condições periodontais em uma população de Bauru, Brasil - Mariana Schützer Ragghianti; Sebastião Luiz Aguiar Greghi; José Roberto Pereira Lauris; Adriana Campos Passanezi Sant'Ana; Euloir Passanezi (University of São Paulo, 2004)
Epidemiology is the study of health and disease in populations, and of how these conditions are influenced by heredity, biology, physical environment, social environment, and personal behavior. There are many epidemiological studies in Brazilian population but few about the influence of some risk factors in periodontal conditions. This cross-sectional study was performed to assess the influence of age, sex, plaque and smoking on periodontal disease in a population from Bauru (Brazil). Data concerning periodontal status were collected from 380 patients in the University of São Paulo (USP). Measurements of periodontal pocket depths (PPD), clinical attachment levels (CAL), plaque index (PI) of four sites in all teeth were registered. The influence of age, sex and smoking habits on the periodontal parameters were statistically evaluated using descriptive statistical and ANOVA. The correlation between plaque and periodontal parameters was analyzed by Pearson's correlation coefficient. The results showed an increase in the mean of periodontal destruction (PPD and CAL) and a higher number of sites with severe losses with increasing age. Correlation among percentage of sites with plaque and periodontal parameters (PPD and CAL) were positive but weakly related. The male group showed significantly higher means of CAL than the female. Smokers had significantly higher PPD and CAL means than non-smokers. Aging, smoking habit, male sex, and percentage of sites with plaque were associated with a great increase of periodontal destruction, being important factors in the diagnosis of the periodontal disease in this Brazilian population. A Epidemiologia é o estudo da saúde e da doença nas populações e de como esses estados são influenciados pela hereditariedade, biologia, ambiente físico e social e comportamento pessoal. Existem vários estudos epidemiológicos na população brasileira porém poucos sobre a influência de fatores de risco nas condições periodontais. Este estudo transversal objetivou avaliar a influência da idade, sexo, placa bacteriana e fumo na doença periodontal em uma amostra da cidade de Bauru. Os dados sobre as condições periodontais foram obtidos de 380 pacientes da Universidade de São Paulo, sendo registradas medidas de profundidade de sondagem, nível de inserção clínica e índice de placa de 4 sítios de todos os dentes. A influência da idade, sexo e fumo foram avaliadas utilizando-se a Estatística descritiva e a Análise de Variância (ANOVA) e o papel da placa bacteriana, por meio do coeficiente de correlação de Pearson. Os resultados mostraram um aumento nas médias de profundidade de sondagem e nível de inserção e um maior número de sítios com perdas severas com o avanço da idade. A correlação entre a porcentagem de sítios com placa e os parâmetros periodontais foi positiva porém fraca. O sexo masculino apresentou médias significantemente maiores de nível de inserção do que o sexo feminino. Os fumantes obtiveram médias significantemente maiores de profundidade de sondagem e de nível de inserção quando comparados aos não-fumantes. A idade, hábito de fumar, sexo masculino e porcentagem de sítios com placa estão associados a maior destruição periodontal, sendo fatores importantes no diagnóstico da doença periodontal nessa população brasileira.